Cinematic virtual reality: How emotional responses vary across movie genre and technological format - Rodrigues, M. B. (2023)
The current study seeks to explore whether virtual reality (VR) can be more effective than traditional 2D in influencing emotional responses (namely, empathy and sympathy), considering different movie genres. A factorial design 2 (movie genre: animation; documentary) x 2 (VR; 2D) between-subjects experiment was employed. A total of 145 participants were recruited. Findings suggest that sympathy and empathy responses to movies are affected by the technological format used to experience a movie, being higher in VR than in 2D. Regarding sympathy, the conducted analysis suggests that the movie genre has a higher impact than the format. Additionally, the present study concludes that the interaction between technological format and movie genre has a significant impact on WOM.